PENGARUH PROMOSI FLASH SALE DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI PADA KONSUMEN SCARLETT DI JEMBER - Wulandari, Deasy; Utami, Mega; Sukarno, Hari; Subagio, N. Ari; Indraningrat, Ketut (Study Program of Management Faculty of Economics and Business University of Jember, 2025)
This research was conducted on consumers who had bought Scarlett in Jember. The aim is to determine the influence of consumers who wish to buy and decide to buy which is influenced by the flash sale promotions and brand ambassadors used by Scarlett. Data collection The method used was a questionnaire with a purposive sampling technique of 190 respondents from Jember who had purchased Scarlett at least once and were aged 20 years and over. Hypothesis test using path analysis with the help of SPSS 25. The results of this study state that: 1) Partial flash sale promotions have a significant influence on buying interest. 2) Brand ambassadors partially have a significant influence on purchasing interest. 3) Partial purchasing interest has a significant influence on purchasing decisions. 4) Partial flash sale promotions have a significant influence on purchasing decisions. Tourist experiences have a positive and significant effect on intention to visit again. 5) Brand ambassadors partially have a significant influence on purchasing decisions. 6) Flash sale promotions partially have a significant effect on purchasing decisions through purchase interest. 7) Brand ambassadors partially have a significant influence on purchasing decisions through purchase interest.